2000
DOI: 10.1021/om990931n
|View full text |Cite
|
Sign up to set email alerts
|

Selective Carbonylation Routes to Thiocarbamates. An Alternative to Phosgene

Abstract: A new route for the synthesis of thiocarbamates using a transition metal complex and CO as a replacement for phosgene has been discovered. The complex (PPh 3 ) 2 PdCl 2 reacts with N-benzylmethylamine, 4-chlorobenzenethiol, and CO to selectively generate a thiocarbamate. Kinetic studies and the isolation of several intermediates in this reaction allow for the proposal of a mechanistic scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
(30 reference statements)
3
22
0
Order By: Relevance
“…The Pd-Cl and Pd-P bond distances (Table 1) are in good agreement with other structurally related compounds, such as trans-[PdCl 2 (NHCy 2 )(PPh 3 )] (Cy is cyclohexyl; Parvez et al, 2004), trans-[PdCl 2 (MeNHCH 2 Ph)-(PPh 3 )] (Jones et al, 2000) and trans-[PdCl 2 (indoline-N)(PPh 3 )] (Chen et al, 1997). In contrast, the Pd-N bond distance is 2.236 (4) Å , far longer than that observed in palladium(II) complexes with secondary amines (Pd-N = 2.121-2.166 Å ; Parvez et al, 2004;Jones et al, 2000;Chen et al, 1997;Albinati et al, 1992). The coordination of palladium has an approximately square-planar geometry (Table 1).…”
Section: Commentsupporting
confidence: 80%
“…The Pd-Cl and Pd-P bond distances (Table 1) are in good agreement with other structurally related compounds, such as trans-[PdCl 2 (NHCy 2 )(PPh 3 )] (Cy is cyclohexyl; Parvez et al, 2004), trans-[PdCl 2 (MeNHCH 2 Ph)-(PPh 3 )] (Jones et al, 2000) and trans-[PdCl 2 (indoline-N)(PPh 3 )] (Chen et al, 1997). In contrast, the Pd-N bond distance is 2.236 (4) Å , far longer than that observed in palladium(II) complexes with secondary amines (Pd-N = 2.121-2.166 Å ; Parvez et al, 2004;Jones et al, 2000;Chen et al, 1997;Albinati et al, 1992). The coordination of palladium has an approximately square-planar geometry (Table 1).…”
Section: Commentsupporting
confidence: 80%
“…A number of mixed-ligand complexes of phosphines and amines have also been reported, e.g. trans-[Pd(PBu 3 )(PhNH 2 )Cl 2 ] (Romm et al, 1995), trans-[Pd(PPh 3 )-(CH 3 NHCH 2 Ph)Cl 2 ] (Jones et al, 2000) and trans-[Pd{P(o-CH 3 Ph) 3 }(NHMe 2 )Cl 2 ] (Paul et al, 1994). In this paper, we report the synthesis and crystal structure of trans-dichloro-(dicyclohexylamine)(triphenylphosphine)palladium(II), (I).…”
Section: Commentmentioning
confidence: 99%
“…Unlike the hit-and-run/combinatorial approach often adopted due to various reasons, the approach described herein involves critical stepwise ligand design strategy. The importance of such an approach is underlined in a number of tri-and tetramerisation of ethylene, and other, catalytic reactivity studies reported in literature [12][13][14][15].…”
Section: Commentmentioning
confidence: 99%
“…The title complex forms part of an ongoing research study on the development of highly effective palladium, and platinum group metals in general, catalysts for various organic transformations [12][13][14][15][16][17][18][19]. The two Cl ligands on the title complex adopt a cis-conformation while the distorted square planar geometry is illustrated by a 93.83(2)°bond angle formed by the P-Pd-P bonds.…”
Section: Commentmentioning
confidence: 99%